Sintesis Komposit Polianilin-Karbon Aktif dari Tongkol Jagung sebagai Elektrolit Padat Pada Baterai - Lela Mukmilah Yuningsih; Yusri Mutia Fauziyah (Syarif Hidayatullah State Islamic University, 2018)
The polyaniline-activated carbon composites are synthesized using aniline chemical oxidation polymerization methods as well as variations in carbonization temperature of 800 °C and 1000 °C. The polyaniline-activated carbon composites are characterized by their value of conductivity, functional groups, crystallinity, morphology, composition and electrical quantities by LCR-meter analysis, FTIR, XRD, SEM-EDX and digital multimeters. The conductivity value of composite polyanilin-activated carbon with carbonization temperature of 800°C and 1000 °C are 0.718 S/cm and 1.1003 S/cm. Polyaniline-activated carbon 800 composite and Polyaniline-activated carbon 1000 composite showed absorption bands acoording to PANI. The wave number that appear on PANI-activated carbon 800 composite and PANI-activated carbon 1000 peak is characteristic of PANI where the wave number 1562 cm-1, 1558 cm-1 is the vibration of the C = N and 1479 cm-1, 1475 cm-1is the vibration of the C = C with slacking off the degree of crystallinity PANI-activated carbon 800 i.e. 23.31% and PANI-activated Carbon 1000 i.e. 37.68%. Analysis of surface morphology and composite element content using SEM-EDX shows that particles of polianilin grows on active carbon fiber and free from impurity. The resulting voltage and current both PANI-Carbon 800 and PANI-carbon 1000 are 1.09 volt 19.74 mA and 1.15 Volts 19.98 mA.